KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SE-GUGUS 2 PURWASARI DALAM MEMBACA PEMAHAMAN MELALUI MODEL FIVES DAN MODEL GUIDED READING - Nirmala, Sri Dewi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Students' critical thinking ability is one of the components developed in 21st Century learning. However, this critical thinking ability is still very minimal and far from expectations, this is supported by the results of international surveys that show a low average value. Likewise, the results of the pretest of critical thinking skills of grade IV elementary school students in Cluster 2 Purwasari showed a low average value. This study aims to determine the improvement of students' critical thinking skills in reading comprehension learning through the use of the FIVES Model and the Guided Reading Model. The study used a quasi-experiment with Static Group Pretest-Postest Design. The results showed that the use of these two models could improve students' critical thinking skills. However, the use of Model FIVES experienced a significant increase compared to the Guided Reading Model. Thus, there is an increase in students' critical thinking skills through the FIVES Model compared to the Guided Reading Model.